The Influence of Advertisement and Financial Capability on Purchase Intention at La Royba Mart - Izzatul Muna (Universitas Darussalam Gontor, 2023)
In the digital era, the pattern for doing digital marketing is experiencing a shift. As competitors increase, it goes hand in hand with consumer interest. The purpose of this research is to determine the influence of advertisement and financial capability on consumer’s purchase intention. This research is important as advertisement and financial capability can influence variations of consumer’s consideration in purchasing decision. The type of study is quantitative research with statistical inference approach. Primary data is taken from the results of questionnaires given to consumers as respondents with a total sample of 50 people. Data analysis technique used are ANOVA F-test, t-test, multiple regression analysis, and coefficient determination (R square). Processing data tool used is Statistical Product and Service Solution (SPSS) version 26. The result of F-test and t-test shows that advertisement (X1) and financial capability (X2) simultaneously and partially have significant influence on consumer’s purchase intention (Y). The result of coefficient determination (R square) shows that 46.2% of factors affecting the consumers intention to purchase at La Royba Mart can be explained by advertisement factor and consumers’ financial capability factor, while the rest 53.8% factors are explained by other factors that are not studied by the author here.Keywords: Advertisement, Financial Capability, Purchase Intention.